Month of the Year Effect and Anomalous Behavior of Stock Prices in India - Mehta, Kiran (Gyan Management Journal, 2010)
study is destined to examine the anomalous patterns in the stock return behavior in India .. - -;; various months of the year. It has examined whether any particular month in the year shows . ·,: :.al distribution of mean returns in comparison to the mean returns rest of the year resulting into returns to the investors. The four major indices of the Bombay Stock Exchange, i.e., (i) : ·
Keywords: Abnormal Returns; Indian Stock Market; Month of the Year Effect; November Effect